Analisis Persepsi Judi Online: Implikasi Sosial-Ekonomi dalam Perspektif Maqashid Syariah di Kota Jambi - Mulazimatul Hasanah Lailiyah; Ridhwan Ridhwan; Muhammad Roihan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study examines public perceptions of the online gambling phenomenon and its social and economic implications from the perspective of maqashid shariah, with a case study of the community in Jambi City. The research aims to: (1) identify and analyze the perceptions of Jambi City residents regarding online gambling, and (2) analyze the social and economic implications of online gambling practices within the framework of maqashid shariah. This study employs a descriptive method with a qualitative approach. Data were collected through observation, semi-structured interviews, and documentation, involving various informants including members of the general public, religious figures, university students, former online gamblers, academics, and law enforcement officers. The data were analyzed using the Miles and Huberman interactive model. The findings reveal that the people of Jambi City generally hold negative perceptions of online gambling, grounded in religious, social, and moral values. Such practices are viewed as deviant behaviors that contradict Islamic teachings and social norms. However, some younger individuals perceive online gambling as a form of entertainment or a quick means to earn money, influenced by environmental factors and digital access. Online gambling has resulted in social consequences such as family breakdowns, reduced social interaction, and domestic conflicts, as well as economic impacts including financial losses, dependence on interest-based loans, and the risk of bankruptcy. From the perspective of maqashid shariah, online gambling contradicts the five fundamental objectives of Islamic law: the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). Therefore, active involvement from the government, religious leaders, educational institutions, and society is essential to comprehensively prevent and address the issue of online gambling in order to safeguard public welfare.